Job Insecurity, Organizational Justice, and Turnover Intention of High-Potential Employees in Crisis - Fikri Zikra Akrama; Diin Fitri Ande (Telaah Bisnis, 2026)
The construction industry is particularly susceptible to economic fluctuations, frequently resulting in restructuring and heightened stress for high-potential employees (HiPo). This study examines the influence of job insecurity and organizational justice on turnover intention, with organizational commitment serving as a mediating variable, focusing on HiPo employees at PT ZX, a state-owned construction company experiencing a crisis. Employing a quantitative approach with 234 respondents, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research draws upon Conservation of Resources (COR) Theory and Social Exchange Theory, testing seven hypotheses regarding both direct and indirect effects. Results indicate that job insecurity has a significant positive effect on turnover intention and a significant negative effect on organizational commitment, whereas organizational justice has no significant direct effect on turnover intention but strongly strengthens organizational commitment. Organizational commitment, in turn, significantly reduces turnover intention and significantly mediates the effects of both job insecurity and organizational justice on turnover intention. These findings contribute to the literature on talent retention and provide practical recommendations for human resource management during crises. The study integrates job insecurity and organizational justice as predictors within a mediation model tailored to the construction sector crisis. Practically, it proposes strategies for BUMN HRM to develop equitable and sustainable talent-retention policies. The evidence further supports SDG 8 (Decent Work and Economic Growth), particularly Targets 8.5 and 8.8, by demonstrating the significance of organizational justice and commitment in sustaining decent work during restructuring in the construction sector.